An Annotated Checklist of Earthworms (Annelida: Clitellata: Oligochaeta) of Indo-Gangetic Plains of India - Tiwari, Nalini; Tiwari, Pooja; Gupta, Neelima; Yadav, Shweta (Zootaxa, 2024)
A checklist of earthworm species hitherto known from Indo–Gangetic Plains of India is presented. In total, 98 species and subspecies are recorded, belonging to 33 genera spread over 9 families. Of these, 38 species are recognized as endemics and 34 as exotics. For every species and subspecies, the checklist comprises state-wise distributional information, all important synonyms, type locality and citations to the original description found in the literature.